ANALISIS KESENJANGAN GENDER DALAM PENYELENGGARAAN JALUR PEJALAN KAKI DI KOTA BANDUNG TAHUN 2024 - Yuan Veriontina Gathari; Antik Bintari (Halu Oleo University, 2025)
This study aims to identify gender gaps in the development of pedestrian paths or sidewalks in Bandung City in terms of Access, Participation, Control, and Benefits (APKM), as well as to determine the background of gender gaps. The study uses a qualitative approach with a case study method through data collection techniques such as interviews, literature studies, and documentation. The analysis shows that the development and rehabilitation of sidewalks in Bandung City are not yet fully gender-responsive because there are still gaps in terms of access, participation, control, and benefits. Although conceptually designed to serve the entire community, the reality on the ground shows that there are significant barriers, especially for vulnerable groups such as women, the elderly, and people with disabilities. To achieve sustainable and equitable development, the Bandung City Water Resources and Public Works Agency needs to integrate a gender perspective more deeply into every stage of pedestrian infrastructure development.